2018
DOI: 10.1111/jopy.12425
|View full text |Cite
|
Sign up to set email alerts
|

Teleological explanation and positive emotion serially mediate the effect of religion on well‐being

Abstract: These results provide evidence of the importance of teleological explanations of daily events in religious enhancement of well-being.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…Concerning the cognitive dimension of SWB, a number of studies found a positive relationship between spirituality as well as religiosity and life satisfaction (Yoon and Lee, 2004). To explain these findings, it has been suggested that people who experience more connection with and direction from a higher power, that is, people who show high religious and spiritual involvement, tend to give a more positive appraisal of their lives (Vishkin et al, 2016, 2019; Ramsay et al, 2019). The sense of being in connection with a higher power, with others, and, in general, with life represents an effective way to maintain a positive evaluation of one’s life, despite all the possible negative circumstances that one may encounter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the cognitive dimension of SWB, a number of studies found a positive relationship between spirituality as well as religiosity and life satisfaction (Yoon and Lee, 2004). To explain these findings, it has been suggested that people who experience more connection with and direction from a higher power, that is, people who show high religious and spiritual involvement, tend to give a more positive appraisal of their lives (Vishkin et al, 2016, 2019; Ramsay et al, 2019). The sense of being in connection with a higher power, with others, and, in general, with life represents an effective way to maintain a positive evaluation of one’s life, despite all the possible negative circumstances that one may encounter.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to Ramsay et al (2019), another important mechanism that can explain the relationship between religiosity and well-being is that of emotional regulation, which consists in the modulation of emotional states functionally to the environment’s demands. To the extent that religion constantly trains people to reassess emotional events, religious individuals may become more used to cognitive reappraisal.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al (2021), for example, in researching the psychology of religion, concern themselves primarily with extrinsic teleological explanation, focusing on artifacts (which have extrinsic teleology), and teleological explanations of ecosystems (i.e., "Earthworms tunnel underground in order to aerate the soil") (p. 1723). Ramsay et al (2018) similarly concern themselves with the relationship between religious orientation and teleological explanation, observing how individuals explain their daily experiences in relation to larger narratives of divine or cosmic purpose (i.e., extrinsic teleology). Stern et al (2018) also occupy themselves with the relation between religion and teleology.…”
Section: The Psychology Of Religion and Extrinsic Teleologymentioning
confidence: 99%
“…The ability to derive meaning has been identified as a possible link in the causal chain between religion and enhanced well-being (Steger & Frazier, 2005), along with other potential mediators such as positive emotions and need satisfaction that will be discussed in subsequent sections. While research has shown that religious individuals see divine purpose and significance in day-to-day events (Ramsay et al, 2018), this ability to derive meaning is even more striking in the case of highly impactful events (Lupfer et al, 1996). This suggests that religion should serve a psychologically protective function when confronted with an unprecedented global emergency such as COVID-19.…”
Section: Religion the Search For Meaning And Well-beingmentioning
confidence: 99%